Changes in the common bean transcriptome in response to secreted and surface signal molecules of Rhizobium etli - Dalla Vía, María Virginia (2015)
Establishment of nitrogen-fixing symbiosis requires the recognition of rhizobial molecules to initiate the development of nodules. Using transcriptional profiling of roots inoculated with mutant strains defective in the synthesis of Nod Factor (NF), exopolysaccharide (EPS), or lipopolysaccharide (LPS), we identified 2,606 genes from common bean (Phaseolus vulgaris) that are differentially regulated at early stages of its interaction with Rhizobium etli. Many transcription factors from different families are modulated by NF, EPS, and LPS in different combinations, suggesting that the plant response depends on the integration of multiple signals. Some receptors identified as differentially expressed constitute excellent candidates to participate in signal perception of molecules derived from the bacteria. Several components of the ethylene signal response, a hormone that plays a negative role during early stages of the process, were down-regulated by NF and LPS. In addition, genes encoding proteins involved in small RNA-mediated gene regulation were regulated by these signal molecules, such as Argonaute7, a specific component of the trans-acting short interfering RNA3 pathway, an RNA-dependent RNA polymerase, and an XH/XP domaincontaining protein, which is part of the RNA-directed DNA methylation. Interestingly, a number of genes encoding components of the circadian central oscillator were down-regulated by NF and LPS, suggesting that a root circadian clock is adjusted at early stages of symbiosis. Our results reveal a complex interaction of the responses triggered by NF, LPS, and EPS that integrates information of the signals present in the surface or secreted by rhizobia.